(untitled) (Economic and Political Thought, 2018)
The aim of the article is to present the most important EU activities in the construction of a European financial safety network, both those already undertaken (including in particular: CRD, CRR and Banking Union) as well as planned (including changes regarding: capital requirements, large exposures, long-term liquidity, financial leverage, risk assessment, reporting of banks and banks referred to as TBTF. In addition, the article assesses the measures taken in the field of financial market regulation from the point of view of three criteria, i.e. stability of the sector, efficiency of banks’ operations and perception of new requirements by banks.